Trends in Musculoskeletal Rehabilitation Needs in China From 1990 to 2030: A Bayesian Age-Period-Cohort Modeling Study - Chen, Ningjing; Fong, Daniel Yee Tak; Wong, Janet Yuen Ha (Frontiers in Public Health, 2022)
Background Disability and medical expenses caused by musculoskeletal disorders in China had a great impact on the global health and economy. Rehabilitation is essential for dealing with musculoskeletal disorders. However, China's musculoskeletal rehabilitation needs remain unknown. This study aimed to examine the secular trends for musculoskeletal rehabilitation needs in China from 1990 to 2030. Methods Data on musculoskeletal rehabilitation needs were extracted from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) repository. Estimated annual percentage changes (EAPCs) were calculated to reflect fluctuations in the age-standardized rates. The Bayesian age-period-cohort models were used to project rehabilitation needs. Results The number of prevalent cases and years lived with disability (YLD) counts in need of musculoskeletal rehabilitation increased greatly in China from 1990 to 2019. There will be 465.9 million Chinese people in need of rehabilitation, with the age-standardized prevalence rate increasing to 21,151.0 [2.5–97.5% predictive interval (95% PI) 14,872.6–27,429.3] per 100,000 persons in 2030. Similarly, the YLD counts will increase to 40.1 million, with the age-standardized YLD rate increasing to 1,811.2 (95% PI 1,232.5–2,390.0) per 100,000 persons in 2030. Conclusions Increasing trends in musculoskeletal rehabilitation needs were found from 1990 to 2019, which will be anticipated through 2030. Rehabilitation is suggested to be integrated into primary care settings.